Biomechanics of Movement in the Japanese Approach to Manicure as a Factor in Reducing Microtrauma - Popovych, Alina (Педагогічна Академія: наукові записки, 2025)
The relevance of this study is determined by the growing occupational risks in the beauty industry associated with prolonged static load, repetitive fine-motor movements, and the lack of ergonomically optimized working conditions. Manicurists belong to a professional category with a high frequency of microtraumas of the hands, forearms, and cervical–shoulder area, which reduces their endurance and quality of work. The Japanese approach to manicure, based on the principles of naturalness, delicacy, and motor balance, provides an effective model for preventing musculoskeletal overloads and can be adapted as a benchmark of ergonomic practice in this field. The aim of the article is to scientifically substantiate the biomechanical principles of manicurist movements in the Japanese technique and to determine their impact on reducing microtraumatization of the musculoskeletal system during professional activity. Methods. The research methodology is based on systemic, anatomical–physiological, and ergonomic approaches using observation, biomechanical analysis, structural comparison, content analysis, and empirical data generalization. To assess the effectiveness of working postures and motor patterns, criteria of body symmetry, load distribution, and micromovement stability were applied. Results. The study identifies optimal anatomical and physiological parameters of working posture, rhythm, and movement amplitude that reduce tension in the forearm, wrist, and cervical–shoulder muscles. It has been proven that a symmetrical body position, neutral wrist alignment, and regulated rhythm and breaks promote stable motor balance and prevent microtrauma development. Scientific and practical recommendations are provided for optimizing workplace ergonomics, selecting tools with a balanced center of gravity, and introducing microbreaks to maintain muscle regeneration. Conclusions. Ergonomic work organization and biomechanically precise movements ensure not only high procedural accuracy but also long-term preservation of the practitioner’s functional stability. Movement optimization is regarded as the foundation of a culture of safe labor in aesthetic services. Prospects for further research include the development of digital biomechanical simulators for training safe motor patterns, standardization of ergonomic parameters for manicurists’ workplaces, and interdisciplinary investigation of the impact of prolonged static loads on the cognitive and motor efficiency of beauty industry professionals.